RELIGION, CUSTOM AND IDENTITY: Conflict Transformation in Banda Neira Islands (State Islamic University (UIN) of Sunan Ampel Surabaya, 2025)
This article deals with the transformation of conflict and the formation of identity of the Bandanese people in the Banda Islands after Maluku conflict through an analysis of kabata, folk songs that record the historical narratives of the colonial era. This research employs a grounded theory approach to collect field data from the Banda Islands and Ambon Island, as well as literature related to the Banda Eli community in Kei Island. The finding indicates that the Maluku conflict had an effect on the diversity of religion, custom and social relation among the Banda people, and led to the fragmentation of identity—the communities of Banda Neira Islands, Banda Eli in Kei and Banda Suli in Ambon—on the basis of religious aspects and their bond to Banda lands. The transformation of conflict created a consolidation of identity of Banda Islands community, which became religiously more exclusive, especially after the rise of conservative Islam in Indonesia. This article fills the gap in the study of kabata by positioning it as a key to understanding how the identity of the Bandanese people has developed and adapted within the context of the long history of colonialism and contemporary conflicts.